Penerapan Model Pembelajaran Student Facilitator And Explaining Untuk Meningkatkan Pemahaman Konsep Matematika Sekolah Dasar - Rahayu, Putri; Fadhilaturrahmi, Fadhilaturrahmi; Kusuma, Yanti Yandri (Jurnal Pendidikan Tuntas, 2024)
The research was motivated by the low results of students' understanding of concepts mathematics conepts in class IV SDN 013 kumantan. One solution to solve this problem is to apply the student facilitator and explaining model. The purpose of this study was to describe increasing students' conceptual understanding in mathematics learning by applying the student facilitator and explaining model to fourth grade students at SDN 013 Kumantan. This research method is classroom action research (CAR) which is carried out in two cycles. Each cycle consists of two meetings and four stages, namely planning, implementation, observation and reflection. The subjects of this study were fourth grade students, totaling 9 students. Data collection techniques in the form of documentation, observation and tests. this is indicated by an increase in the number of students who reach the minimum completeness criteria (KKM) and an increase in the average and classical grades. before action 50.55 cycle I meeting I 65.75 and cycle I meeting II 67.6 increased up to cycle II meeting I to 81.47 and cycle II meeting II to 82.4. Likewise with classical completeness from before the action 22.2%, the first cycle of the first meeting 44.4% and the first cycle of the second meeting 66.7% and increased in the second cycle of the first meeting to 77.8%, and the second cycle of the second meeting 88, 9%.